TESOL Strategies for the Mathematics Classroom - Sally Robinson (Asociación Colombiana de Profesores de Ingles, 2017)
Teaching mathematics becomes especially challenging when including the needs of the limited English proficient students who struggle with language and cultural issues. However, many strategies exist that can ease the difficulty involved in providing a quality mathematics experience. The strategies to help the limited English proficient student are separated into three specific categories: literacy development strategies, cultural harmony strategies, and effective instructional strategies. Each category has specific suggestions and real class examples that make teaching mathematics to ALL more than just a possibility.